The Effect of Using Talking Stick Learning Model on Student Learning Outcomes in Islamic Primary School of Jamiatul Khair, Ciledug Tangerang - Saihu Saihu (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2020)
This study aims to determine the effect of using a Talking Stick model on learning outcomes of Fiqh. The research method used was a quasi-experimental study with a non-equivalent control group design. The population in this study was all students at the Fourth Grade of Islamic Primary School of Jamiatul Khair Ciledug-Tangerang, Sampling was drawn by using a saturated sampling technique in which all populations were used as samples consist of the control class and the experimental class. The instrument of this was a multiple-choice test that has four options. Moreover, the data analysis technique utilized the t-test. The results of the study showed that the mean score of the posttest for the control class was 69.8. Meanwhile, the mean score of the posttest for the experimental class was 77.76 with the standard deviations were 8.55 and 10.02 respectively. Furthermore, the result of the t-test showed that t-count (3,021)> t-table (2,011). This means that the t-count is bigger than the t-table. In other words, we can conclude that there is a significant difference between students who have studied by using the Talking Stick model and students who used conventional techniques.